Zarich Product - Ayob, Mohd Afiz Huzairi; Md Zaki, Md Izzat Hafifi; Christopher Chin, Cosmas Ken; Donny, Hebrry; Abd Rahman, Riduwan; Yunus, Muhammad Zaid (2016)
ZARICH Enterprise is a partnership form of business that manufacturing and selling high sophisticated toilet located in , Imago Shopping Mall, KK Times Square Phase 2, Off Coastal Highway, 88100 Kota Kinabalu, Sabah, for marketing and distribution. Our firm also had a factory which located at , KKIP Selatan, 88450 Kota Kinabalu, Sabah. Our customers basically target on high and middle income and other businesses such as hotels, shopping mall, and housing developer that focusing luxuries and quality concept. In addition, we discover that no other manufacturing company that produce a high sophisticated toilet especially in Malaysia. In that moment we saw an opportunity and become pioneer in a high sophisticated toilet manufacturing industries. With our firm establishment, Malaysia not necessary focussed on imported goods in order to fulfil the demand from society. We managed to save a millions of cash outflows from imported activities. Our product had an innovation from ordinary high tech toilet such as automatic and manual mode. We hope our product become part of Malaysian's life living such as Japanese society living which concern about the hygiene all over the time. Our invention makes a huge transformation in society and economic terms.